The Active Recovery Triad Model: A New Approach in Dutch Long-Term Mental Health Care - Zomer, Lieke J. C.; Voskes, Yolande; van Weeghel, Jaap; Widdershoven, Guy A. M.; van Mierlo, Tom F. M. M.; Berkvens, Bram S.; Stavenuiter, Bert; van der Meer, Lisette (Frontiers in Psychiatry, 2020)
Unlike developments in short-term clinical and community care, the recovery movement has not yet gained foothold in long-term mental health services. In the Netherlands, approximately 21.000 people are dependent on long-term mental health care and support. To date, these people have benefited little from recovery oriented care, rather traditional problem oriented care has remained the dominant approach. Based on the view that recovery is within reach, also for people with complex needs, a new care model for long-term mental health care was developed, the Active Recovery Triad (ART) model. In a period of two and a half years, several meetings with a large group of stakeholders in de field of Dutch long-term mental health care took place in order to develop the ART model. Stakeholders involved in the development process were mental health workers, policy advisors, managers, directors, researchers, peer workers and family representatives. The ART model combines an Active role for professionals, service users and significant others, with focus on Recovery and cooperation between service users, family and professionals in the Triad. The principles of ART are translated into seven crucial steps in care and a model fidelity scale in order to provide practical guidelines for teams implementing the ART model in practice. The ART model provides guidance for tailored recovery oriented care and support to this ‘low volume high needs’ group of service users in long-term mental health care, aiming to alter their perspective and take steps in the recovery process. Further research should investigate the effects of the ART model on quality of care, recovery and autonomy of service users and cooperation in the triad.